Proposed improvement of coastal habitat resilience: The case study of Pantano forest of Policoro in southern Italy - Mirauda, Domenica; De Donato, Rocco; Santandrea, Giuseppe (Frontiers in Marine Science, 2022)
In the last decades, climate change and the rapid urbanization due to the development of the coastal economy have led to biodiversity loss and the fragmentation of habitat in many coastal zones. The presence of protected areas cannot prevent the progress of land degradation. However, these areas are very important because they provide significant ecosystem services and affect local tourism. With regard to increasing adaptation strategies to human pressures and climate change, the present study proposes a detailed monitoring activity and an ecological restoration plan which could improve the resilience of a protected coastal zone in the Pantano forest of Policoro, located on the Ionian coast (southern Italy). In this area, continuous phenomena of intensive deforestation, hydraulic reclamation actions, and fires have reduced the native species of particular naturalistic value, favouring the advancement of desertification, coastal erosion, and saltwater intrusion. The proposed actions are derived from a preliminary analysis on maps, UAV-images, climate data and from meetings with the local community. The operative process detailed in this article could be applied to other protected areas which are subjected to the same phenomena and problems.